Bone Mineral Density Values Using Radiofrequency Echographic Multi-Spectrometry in Premenopausal Breast Cancer Patients Receiving Tamoxifen Therapy - Russarianto, Heru; Irsyam, Ilham Abdullah; Bariqi, Muhammad Ilmam; Kadar, Pranajaya Dharma; Mohd Kamil, Muhammad Kashani ((JOINTS) Journal Orthopaedi and Traumatology Surabaya, 2025)
Background: Breast cancer (BC) is the most prevalent malignancy in women. Tamoxifen produces varying effects on the bone according to menopausal status. This study was performed at Adam Malik Hospital to analyze the risk factors for osteoporosis, focusing on bone mineral density (BMD) and length of tamoxifen therapy in premenopausal breast cancer patients. This research also used radiofrequency echographic multi-spectrometry (REMS) to evaluate BMD as a potential alternative to dual x-ray absorptiometry (DXA) in the diagnosis of osteoporosis patients. Methods: This case-control study analyzed and interviewed 20 premenopausal breast cancer patients who received at least one year of tamoxifen therapy. The stadium of cancer, type of tamoxifen therapy, and BMD of each patient were determined using REMS. Results: The study of 20 breast cancer patients showed a mean age of 50.4 ± 5.61 years. The average length of tamoxifen therapy was 2.65 years, with a standard deviation of 1.13 years. Most patients presented with osteopenia status, namely 16 patients (80%), whereas three patients (15%) of the total sample presented with osteoporosis. REMS showed excellent accuracy in distinguishing between various tissue types, providing detailed information on tissue composition and structure. Conclusions: Based on the conducted research, it was determined that the use of tamoxifen for more than four years in premenopausal breast cancer patients influenced the incidence of osteoporosis. REMS shows potential as an alternative to DXA for the diagnosis of osteoporosis.